Resilience and whistleblowers: Coping with the consequences. Issue 4 (1st October 2016) - Uys, Tina; Smit, Ria
ABSTRACT: Understanding the whistleblower's ability to cope with the repercussions of showing 'ethical resistance' in the workplace is a neglected area of research. Drawing on qualitative data from narrative interviews with whistleblowers in South Africa, this article analyses the ways in which whistleblowers deal with the hostile responses from employers that tend to follow their disclosures. Most of the participants employed successful coping mechanisms showing that they remained hopeful that justice would prevail, even amidst emotions of distress and fear due to organisational reprisal. The study showed that the resilience perspective is an important frame for understanding whistleblowers' responses to the challenging consequences of their actions. Practitioners should consider ways to enhance individual resilience to ensure a positive outcome of disclosures of organisational wrongdoing.